Hubungan Antara Dukungan Sosial Orang Tua Dengan Student Well Being Pada Siswa di MTS Nurul Anwar Pengguna Sistem Full Day School - Permatasari, Wahyuning Tyas; Fitriani, Yulia; Pertiwi, Yuarini Wahyu (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
Student well-being is a condition where a student feels safe, happy, satisfied with themselves and their surroundings, so that students are able to carry out their roles and functions at school effectively. With social support from parents, students will tend to feel more confident because they feel cared for and cared for by their parents. Especially for students who go to school with a full-day school system, where students spend their longer time from morning to evening for five consecutive days. Positive parental social support is very necessary in children's education. This study aims to determine the relationship between social support from parents and student well-being in MTS students. The sampling technique in this study used the Probability Sampling method with Cluster Random Sampling with 112 respondents consisting of each class level. This instrument uses a modified student well-being scale from Kurniastuti and Azwar and a modified parental social support scale from Adzani. The data in this study used Pearson product moment correlation testing through IBM SPSS (Statistics Package For Social Science) software. The results of this study indicate that there is a relationship between parental social support and student well-being. The relationship between the two variables is in a positive direction, meaning that if students who receive high social support from their parents, then the student well-being owned by the students is also high. Thus, it can be concluded that the alternative hypothesis (Ha) is accepted. Suggestions for further researchers to dig deeper into the factors that influence student well-being.